The Influence of the Mind Mapping Assisted PBL Model on the Critical Thinking Ability of Fifth Grade Elementary School Students - Asih, Luh Putu Adi Merta; Wiyasa, I Komang Ngurah (Universitas Pendidikan Ganesha, 2023)
Currently, there are still many teachers who use conventional learning systems, which are teacher-centred so that students' roles tend to be passive during learning. Student passivity also affects students' critical thinking abilities. Research purposesto analyze the influence of the problem based learning model assisted by mind mapping on students' critical thinking abilities in class V science material. The research included a quasi-experiment with a nonequivalent control group design research design. The population of this study was all fifth grade students in elementary school, totaling 160 students. The data collection method in this research is the essay test method which consists of 9 validated questions. The research data were analyzed using descriptive statistical analysis techniques and inferential statistical analysis techniques. The data obtained were analyzed using the t-test with the separated variance formula. The results of the research analysis show that tcount = 3.825 and ttable = 2.009 at the 5% significance level (α = 0, 05) with degrees of freedom (dk) = n_1+ n_2-2 = 26 + 26 - 2 = 50. So, it is found that tcount (3.825) > ttable (2.008) so that H0 is rejected. Based on these results, it can be concluded that there is a significant difference in students' critical thinking abilities in science material who follow the Problem Based Learning learning model assisted by mind mapping and students who are not taught using the learning model in class V elementary.